Proportion of time spent in blood glucose range 70 to 140 mg/dL is associated with increased survival in patients admitted to ICU after cardiac arrest: A multicenter observational study - Zhou, Dawei (Medicine (Baltimore), 2020)
The benefit of any specific target range of blood glucose (BG) for post-cardiac arrest (PCA) care remains unknown. We conducted a multicenter retrospective study of prospectively collected data of all cardiac arrest patients admitted to the ICUs between 2014 and 2015. The main exposure was BG metrics during the first 24 hours, including time-weighted mean (TWM) BG, mean BG, admission BG and proportion of time spent in 4 BG ranges (<= 70 mg/dL, 70–140 mg/dL, 140–180 mg/dL and > 180 mg/dL). The primary outcome was hospital mortality. Multivariable logistic regression, Cox proportion hazard models and generalized estimating equation (GEE) models were built to evaluate the association between the different kinds of BG and hospital mortality. 2,028 PCA patients from 144 ICUs were included. 14,118 BG measurements during the first 24 hours were extracted. According to TWM-BG, 9 (0%) were classified into the <= 70 mg/dL range, 693 (34%) into the 70 to 140 mg/dL range, 603 (30%) into the 140 to 180 mg/dL range, and 723 (36%) into the > 180 mg/dL range. Compared with BG 70 to 140 mg/dL range, BG 140 to 180 mg/dL range and > 180 mg/dL range were associated with higher hospital mortality probability. Proportion of time spent in the 70 to 140 mg/dL range was associated with good outcome (odds ratio 0.984, CI [0.970, 0.998], P = .022, for per 5% increase in time), and > 180 mg/dL range with poor outcome (odds ratio 1.019, CI [1.009, 1.028], P< .001, for per 5% increase in time). Results of the 3 kinds of statistical models were consistent. The proportion of time spent in BG range 70 to 140 mg/dL is strongly associated with increased hospital survival in PCA patients. Hyperglycemia (> 180 mg/dL) is common in PCA patients and is associated with increased hospital mortality.